Respectful Maternity Care during Childbirth among Women in a Rural Area of Northern India - Ravneet Kaur; Tejbeer Singh; Mani Kalaivani; Kapil Yadav; Sanjeev K. Gupta; Shashi Kant (Indian Journal of Community Medicine)
Background: Respectful maternity care (RMC) is increasingly being accepted as an essential element for health systems. Every childbearing woman has a right to get dignified and respectful healthcare. Initial research has highlighted that disrespect and abuse are widespread, however, there is a paucity of quantitative evidence. Materials and Methods: In this community-based cross-sectional study, among 485 participants, conducted in 28 villages of Northern India, we ascertained the experience of RMC during childbirth by using the person-centered maternity care (PCMC) scale. Results: The majority (88.7%) of women experienced RMC. The domain with the lowest score was communication and autonomy (62.9%), followed by supportive care (76.1%). Self-introduction by health providers, the position of choice during delivery, relief from pain, and availability of preferred companions during delivery were the deficient areas. Women who gave birth in private health facilities were more likely to receive RMC than those who gave birth in government facilities, while those belonging to marginalized social groups had lesser odds of receiving RMC as compared to other women. Conclusion: Communication skills should be promoted to maternity care providers. Self-introduction by healthcare providers and choice of position during delivery are the deficient areas, which should be focused upon.